»Sicher in Kreuzberg« Constructing Diasporas: Turkish Hip-Hop Youth in Berlin - Kaya, Ayhan (Kultur und soziale Praxis, 2001)
This book examines the construction and articulation of diasporic cultural identity among the Turkish working-class youth in Kreuzberg (Little Istanbul), Berlin. This work primarily suggests that the contemporary diasporic consciousness is built on two antithetical axes: particularism and universalism. The presence of this dichotomy derives from the unresolved historical dialogues that the diasporic youths experience between continuity and disruption, essence and positionality, tradition and translation, homogeneity and difference, past and future, 'here' and 'there', 'roots' and 'routes', and local and global.